Customer Relationship Management Systems (CRM) and Loyalty in the financial sector. (LACCEI, 2024)
The financial sector promotes the growth of national economies, providing financial services and products that enable capital resources for organizations, allowing their growth and expansion. In this sense, to achieve success in organizations that operate in such a complex market and of such importance for the development of countries, it is necessary to promote technology aligned to the use of customer relationship management systems, seeking to better understand their needs and meet them satisfactorily with the aim of generating a commitment to the brand or company. It was considered that there is an average positive relationship between CRM and customer loyalty with a spearman correlation coefficient of 0.540, which allows validating that companies immersed in this sector need to take advantage of digitization and technological tools to respond to the needs of its customers, whose response to this will be loyalty and fidelity, which translates into long-term competitiveness.